Finite element thermo-mechanical analysis of concrete box-girders. (October 2021) - Abid, Sallal.R.; Tayşi, Nildem; Özakça, Mustafa; Xue, Junqing; Briseghella, Bruno
Abstract: A full-scale 3D thermo-mechanical Finite Element (FE) model was conducted in this research to investigate the effect of open-field thermal loads on the structural response of box-girder bridges. A box-girder bridge with a span of 50 m was analyzed for temperature, radiation and displacement fields using COMSOL Multiphysics. To verify the FE model, a full-scale experimental box-girder segment was constructed and instrumented with temperature, radiation and other sensors. From the experimental records, three days with extreme temperature and radiation measurements were selected. The stresses and displacements are discussed at specific points along the 24 h of the selected days and at specific times along critical sections. The FE analysis showed that the vertical and lateral stress distributions exhibited approximately similar behaviors to their corresponding temperature distributions with minor differences but with reversed sign. The results also showed that the maximum stress was compressive, which was −3.35 MPa in summer −3.83 MPa in winter. On the other hand, the maximum vertical and lateral displacements were 12.5 and 1.2 mm, respectively in summer and 2.7 and 1.9 mm in winter.